MULTIKULTURALISME: BELAJAR DARI MASYARAKAT PERDESAAN - Robert Siburian (Masyarakat Indonesia, 2017)
Through this paper, I would like to explain how multiculturalism was implemented by the citizens in Kerta Buana village. The multiculturalism values had been implemented since the government of Indonesia located them at there. Those values of multiculturalism are important to be implemented because transmigrants who were alocated in Kerta Buana village came from various places and different religions and cultures, such as Hindu-Bali and Islam-Java came from Bali island, and Sasak-Lombok came from Lombok island. The differences had became a conflict potention if those differences fail to be managed. Public figures of each society and religion group understood on the situation, so they pushed each their group to live together with other society. Although they did not know what multiculturalism was, the values of multiculturalism had been implemented by them. We can see the multiculturalism of community in Kerta Buana village through their everyday life.Keywords: Multiculturalism, value, transmigration, culture, religion, and Kerta Buana Village. ABSTRAKTulisan ini menjelaskan bagaimana multikulturalisme diimplementasikan oleh masyarakat yang bermukim di Desa Kerta Buana. Nilai-nilai multikulturalisme itu telah diterapkan sejak pemerintah Indonesia menempatkan mereka di lokasi yang baru itu sebagai peserta transmigrasi. Implementasi dari nilai-nilai itu penting karena para transmigran di desa yang jauh dari asal mereka datang dari berbagai tempat dengan agama dan kebudayaan yang berbeda. Perbedaan itu berpotensi menciptakan konflik apabila gagal dikelola. Tokoh dari setiap kelompok masyarakat dan agama memahami perbedaan itu, sehingga mereka mendorong setiap kelompok agar dapat hidup bersama. Meskipun masyarakat di Desa Kerta Buana tidak memahami konsep multikulturalisme, secara tidak sadar bahwa nilai-nilai multikulturalisme itu sudah mereka aplikasikan dalam kehidupan sehari-hari. Lewat tulisan ini, kita dapat melihat masyarakat multikulturalisme di Desa Kerta Buana melalui kehidupan yang mereka jalani.Kata Kunci: Multikulturalisme, nilai, transmigrasi, kebudayaan, agama, dan Desa Kerta Bu